2001
DOI: 10.1046/j.1198-743x.2001.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Clostridium difficile strains isolated from asymptomatic individuals and from diarrheal patients

Abstract: These results revealed the occurrence of three distinct clusters from different wards in Siriraj Hospital. The toxigenic C. difficile of PFGE type A and related subtypes was a predominant infective clone in adult patients, whereas non-toxigenic C. difficile types B2 and D were encountered in asymptomatic infants. This information can be useful in epidemiologic investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…In 2001, Wongwanich et al. [15] reported the prevalence of C. difficile among adult patients to be 25.0% (33/132) and that of toxigenic strains to be 13.6% (18/132). Although the prevalence of toxigenic C. difficile was slightly higher than that observed in the current study, it is still likely to be an underestimation at the time, as the authors only investigated the presence of tcdA.…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, Wongwanich et al. [15] reported the prevalence of C. difficile among adult patients to be 25.0% (33/132) and that of toxigenic strains to be 13.6% (18/132). Although the prevalence of toxigenic C. difficile was slightly higher than that observed in the current study, it is still likely to be an underestimation at the time, as the authors only investigated the presence of tcdA.…”
Section: Discussionmentioning
confidence: 99%
“…This strain was responsible for a high proportion (19.4 %) of C. difficile toxin positive stools in symptomatic children in a recent study in the USA [52]. A study of hospitalised but asymptomatic children in Thailand demonstrated relatively high carriage rates for C. difficile (11.0 % of infants, and 21.1 % of 1-11 year olds) but low rates of toxin A gene detection (0.9 % of infants and none of the older children; toxin B not tested) [53]. 87.2 % of the strains isolated in asymptomatic children in the Japanese day-care study were also non-toxigenic ( tcdA−/tcdB−) [13].…”
Section: Explanations For High Levels Of Asymptomatic Colonisationmentioning
confidence: 92%
“…In this study, tcdA PCR-negative isolates predominated, numbering 57 overall and 18/33 adult diarrhoeal isolates. Fourteen PFGE pulsotypes and eight subtypes were found [57]. No data on circulating ribotypes have been reported.…”
Section: Introductionmentioning
confidence: 99%